1996
DOI: 10.1063/1.116229
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanically driven rapid crystallization of amorphous Si3N4 ceramics

Abstract: The effect of high-energy ball milling on the structure of nanometer sized amorphous ceramics, a-Si3N4 and a-Si–N–C, respectively, has been investigated. At high milling intensity, a-Si3N4 may rapidly crystallize into a mixture of α-Si3N4 and β-Si3N4 after the initial 4 s of milling whereas no structural changes were observed at low milling intensity. For a-Si–N–C, mechanical milling does not cause structural changes at both low and high intensity. It was found that extension of mechanical milling of these har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, the diffusion of atoms is rather localized, thus, in order to complete such in-situ synthesis reaction, the driving force for growing of the Mg 2 Si new phase is necessary. Fan et al [11] reported the mechanically driven rapid crystallization of amorphous Si 3 N 4 , and concluded that the crystallization of a-Si 3 N 4 could be attributed to the presence of mechanical force applied by the milling balls and vials during mechanical milling. According to the results of XRD and microstructures, it is suggested that the RPW process can provide a excess driving force for synthesized Mg 2 Si like the ball milling, and it will facilitate the in-situ synthesie reaction completely.…”
Section: Resultsmentioning
confidence: 99%
“…However, the diffusion of atoms is rather localized, thus, in order to complete such in-situ synthesis reaction, the driving force for growing of the Mg 2 Si new phase is necessary. Fan et al [11] reported the mechanically driven rapid crystallization of amorphous Si 3 N 4 , and concluded that the crystallization of a-Si 3 N 4 could be attributed to the presence of mechanical force applied by the milling balls and vials during mechanical milling. According to the results of XRD and microstructures, it is suggested that the RPW process can provide a excess driving force for synthesized Mg 2 Si like the ball milling, and it will facilitate the in-situ synthesie reaction completely.…”
Section: Resultsmentioning
confidence: 99%
“…within the shear bands, as previously reported. [5][6][7][8][9][10][11] The localized plastic deformation within the shear bands causes a sudden temperature rise in the BMG alloys, [9,[12][13][14][15][16][17][18][19] which results in a dramatic softening of the material. Such softening of the materials can lead to a catastrophic propagation of a single dominant shear band and the eventual fracture of the BMG alloys.…”
Section: Introductionmentioning
confidence: 99%